2022
DOI: 10.1186/s41239-022-00334-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the applicability of virtual reality- enhanced education on extrovert and introvert EFL learners’ paragraph writing

Abstract: During the past decade, Virtual reality (VR)-enhanced education has been adopted as a pedagogically new learning approach to smooth the learning progress. With the rise of VR-enhanced activities, investigating the effect of personality types of EFL learners on their writing performance to use VR-based instruction for learning may be a crucial factor influencing their achievement. This study was an attempt to research the impact of VR- enhanced classes on paragraph writing of extrovert and introvert English for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Eleven of the reviewed studies revealed a positive relationship between BL and EFL university student engagement (Ali et al, 2023;Alghofaili, 2022;Aydın & Çakır, 2022;Chen, 2022;Dousti & Amirian, 2023;Huang et al, 2022;Khodabandeh, 2022;Mohamed, 2022;Qays et al, 2022;Zhao et al, 2023), motivation Aydın & Çakır (2022); Chang (2023); Chen (2022); Mohamed, (2022); Qays et al (2022), and autonomy (Alghofaili, 2022;Aydın & Çakır, 2022;Chen, 2022;Huang et al, 2022;Khodabandeh, 2022;Qays et al, 2022). In a study done by Chen (2022), mixed-methods research was used to assess the efficacy of BL in enhancing student autonomy.…”
Section: Effects Of Bl On Student Engagement Motivation and Autonomy ...mentioning
confidence: 99%
“…Eleven of the reviewed studies revealed a positive relationship between BL and EFL university student engagement (Ali et al, 2023;Alghofaili, 2022;Aydın & Çakır, 2022;Chen, 2022;Dousti & Amirian, 2023;Huang et al, 2022;Khodabandeh, 2022;Mohamed, 2022;Qays et al, 2022;Zhao et al, 2023), motivation Aydın & Çakır (2022); Chang (2023); Chen (2022); Mohamed, (2022); Qays et al (2022), and autonomy (Alghofaili, 2022;Aydın & Çakır, 2022;Chen, 2022;Huang et al, 2022;Khodabandeh, 2022;Qays et al, 2022). In a study done by Chen (2022), mixed-methods research was used to assess the efficacy of BL in enhancing student autonomy.…”
Section: Effects Of Bl On Student Engagement Motivation and Autonomy ...mentioning
confidence: 99%
“…As they provide immersive experiences that can help students to better understand and retain new information. For example, a virtual classroom allows students to interact with a virtual teacher and other students in a virtual environment (Cai & Zhao, 2021 ), while augmented reality (Annamalai et al, 2022 ) and VR (Khodabandeh, 2022 ) can be used to create interactive language learning experiences that simulate real-life situations. Research has shown that these technologies can improve language acquisition, particularly for vocabulary and grammar" (Kondratiuk et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The subject of AR and VR in the online education domain have been explored through experiments in teaching and learning environment (Khodabandeh, 2022; Hsieh, 2021; Avanzato, 2018). Some other scholars have investigated AR and VR experiences of teachers and learners using survey and questionnaires (Low et al ., 2022; Vagg et al ., 2020; Luo et al ., 2017).…”
Section: Review Of Literaturementioning
confidence: 99%